Modelling the fluid forces of the dive start in competitive swimming - Kiuchi, H.; Nakashima, M.; Cheng, K. B.; Hubbard, M. (Journal of Biomechanical Science and Engineering, 2010)
The objective of this study was to construct a fluid force model for the dive start. The fluid force model is incorporated into a swimming human simulation model SWUM, which has been developed by the authors. In order to identify the fluid force coefficients in the model, dive starts performed by actual swimmers were filmed and reproduced by the simulation model. The fluid force coefficients were determined so that the swimmers` movement in the simulation agreed with that of the experiment as much as possible. From simulations using the identified fluid force coefficients, it was found that simulation results of normal and `intentionally bad form` trials for one subject agreed well with the experimental ones. This suggests that the proposed fluid force model would be valid to reproduce dive starts of various forms. For trials of another subject, the discrepancy between simulation and experiment becomes somewhat larger. This error can be reduced, however, by tuning the fluid force coefficients. This indicates that tuning the fluid force coefficients is effective to improve the accuracy of the simulation, and that the proposed model for the fluid forces will be valid for other swimmers